GE_GERICHTE A/1173/2011 vom 25. August 2011 - GE Cour de justice (2011)
Poursuite pour effet de change. Exigeances de forme. Pas d'examen du fond de la créance. Délai. | LP.20; LP.177; LP.178.1; LP.178.2.3. CO 1096